"It is not about us; it is never about us": An Analysis of the Alliance of Jamaican Alumni Associations (AJAA) in Canada, 1980s-2000s - Suliman, Arshad (IYARIC, 2024)
Using the Alliance of Jamaica Alumni Associations (AJAA) as a case study, this paper demonstrates that the Jamaican diasporic community in Toronto created organizations as vehicles of cultural retention, community responses to anti-immigrant and anti-Black racism, and community development—both in the host and home countries.